2.2.103 Problems 10201 to 10300

Table 2.207: Main lookup table. Sorted sequentially by problem number.

#

ODE

CAS classification

Solved?

time (sec)

10201

\[ {}x^{2 n +1} y^{\prime }-a y^{3}-b \,x^{3 n} = 0 \]

[[_homogeneous, ‘class G‘], _Abel]

7.779

10202

\[ {}x^{m \left (n -1\right )+n} y^{\prime }-a y^{n}-b \,x^{n \left (m +1\right )} = 0 \]

[[_homogeneous, ‘class G‘]]

2.644

10203

\[ {}\sqrt {x^{2}-1}\, y^{\prime }-\sqrt {y^{2}-1} = 0 \]

[_separable]

8.688

10204

\[ {}\sqrt {-x^{2}+1}\, y^{\prime }-y \sqrt {y^{2}-1} = 0 \]

[_separable]

10.921

10205

\[ {}\sqrt {a^{2}+x^{2}}\, y^{\prime }+y-\sqrt {a^{2}+x^{2}}+x = 0 \]

[_linear]

1.592

10206

\[ {}x y^{\prime } \ln \left (x \right )+y-a x \left (1+\ln \left (x \right )\right ) = 0 \]

[_linear]

1.425

10207

\[ {}x y^{\prime } \ln \left (x \right )-y^{2} \ln \left (x \right )-\left (2 \ln \left (x \right )^{2}+1\right ) y-\ln \left (x \right )^{3} = 0 \]

[_Riccati]

2.676

10208

\[ {}\sin \left (x \right ) y^{\prime }-y^{2} \sin \left (x \right )^{2}+\left (\cos \left (x \right )-3 \sin \left (x \right )\right ) y+4 = 0 \]

[_Riccati]

9.868

10209

\[ {}\cos \left (x \right ) y^{\prime }+y+\left (1+\sin \left (x \right )\right ) \cos \left (x \right ) = 0 \]

[_linear]

2.963

10210

\[ {}\cos \left (x \right ) y^{\prime }-y^{4}-y \sin \left (x \right ) = 0 \]

[_Bernoulli]

6.717

10211

\[ {}\sin \left (x \right ) \cos \left (x \right ) y^{\prime }-y-\sin \left (x \right )^{3} = 0 \]

[_linear]

4.171

10212

\[ {}\sin \left (2 x \right ) y^{\prime }+\sin \left (2 y\right ) = 0 \]

[_separable]

17.902

10213

\[ {}\left (a \sin \left (x \right )^{2}+b \right ) y^{\prime }+a y \sin \left (2 x \right )+A x \left (a \sin \left (x \right )^{2}+c \right ) = 0 \]

[_linear]

13.741

10214

\[ {}2 f \left (x \right ) y^{\prime }+2 f \left (x \right ) y^{2}-f^{\prime }\left (x \right ) y-2 f \left (x \right )^{2} = 0 \]

[_Riccati]

1.067

10215

\[ {}f \left (x \right ) y^{\prime }+g \left (x \right ) s \left (y\right )+h \left (x \right ) = 0 \]

[NONE]

1.301

10216

\[ {}y y^{\prime }+y+x^{3} = 0 \]

[_rational, [_Abel, ‘2nd type‘, ‘class A‘]]

0.753

10217

\[ {}y y^{\prime }+a y+x = 0 \]

[[_homogeneous, ‘class A‘], _rational, [_Abel, ‘2nd type‘, ‘class A‘]]

10.010

10218

\[ {}y y^{\prime }+a y+\frac {\left (a^{2}-1\right ) x}{4}+b \,x^{n} = 0 \]

[_rational, [_Abel, ‘2nd type‘, ‘class A‘]]

2.367

10219

\[ {}y y^{\prime }+a y+b \,{\mathrm e}^{x}-2 a = 0 \]

[[_Abel, ‘2nd type‘, ‘class A‘]]

1.518

10220

\[ {}y y^{\prime }+y^{2}+4 x \left (x +1\right ) = 0 \]

[[_homogeneous, ‘class D‘], _rational, _Bernoulli]

2.088

10221

\[ {}y y^{\prime }+a y^{2}-b \cos \left (x +c \right ) = 0 \]

[_Bernoulli]

2.830

10222

\[ {}y y^{\prime }-\sqrt {a y^{2}+b} = 0 \]

[_quadrature]

8.685

10223

\[ {}y y^{\prime }+x y^{2}-4 x = 0 \]

[_separable]

2.013

10224

\[ {}y y^{\prime }-x \,{\mathrm e}^{\frac {x}{y}} = 0 \]

[[_homogeneous, ‘class A‘], _dAlembert]

3.923

10225

\[ {}y y^{\prime }+f \left (x^{2}+y^{2}\right ) g \left (x \right )+x = 0 \]

[NONE]

2.621

10226

\[ {}\left (1+y\right ) y^{\prime }-y-x = 0 \]

[[_homogeneous, ‘class C‘], _rational, [_Abel, ‘2nd type‘, ‘class A‘]]

5.532

10227

\[ {}\left (y+x -1\right ) y^{\prime }-y+2 x +3 = 0 \]

[[_homogeneous, ‘class C‘], _rational, [_Abel, ‘2nd type‘, ‘class A‘]]

4.812

10228

\[ {}\left (y+2 x -2\right ) y^{\prime }-y+x +1 = 0 \]

[[_homogeneous, ‘class C‘], _rational, [_Abel, ‘2nd type‘, ‘class A‘]]

4.056

10229

\[ {}\left (y-2 x +1\right ) y^{\prime }+y+x = 0 \]

[[_homogeneous, ‘class C‘], _rational, [_Abel, ‘2nd type‘, ‘class A‘]]

4.032

10230

\[ {}\left (y-x^{2}\right ) y^{\prime }-x = 0 \]

[_rational, [_1st_order, ‘_with_symmetry_[F(x)*G(y),0]‘], [_Abel, ‘2nd type‘, ‘class C‘]]

1.017

10231

\[ {}\left (y-x^{2}\right ) y^{\prime }+4 x y = 0 \]

[[_homogeneous, ‘class G‘], _rational, [_Abel, ‘2nd type‘, ‘class A‘]]

2.346

10232

\[ {}\left (y+g \left (x \right )\right ) y^{\prime }-f_{2} \left (x \right ) y^{2}-f_{1} \left (x \right ) y-f_{0} \left (x \right ) = 0 \]

[[_Abel, ‘2nd type‘, ‘class A‘]]

7.812

10233

\[ {}2 y y^{\prime }-x y^{2}-x^{3} = 0 \]

[_rational, _Bernoulli]

1.576

10234

\[ {}\left (2 y+x +1\right ) y^{\prime }-2 y-x +1 = 0 \]

[[_homogeneous, ‘class C‘], _rational, [_Abel, ‘2nd type‘, ‘class A‘]]

1.960

10235

\[ {}\left (2 y+x +7\right ) y^{\prime }-y+2 x +4 = 0 \]

[[_homogeneous, ‘class C‘], _rational, [_Abel, ‘2nd type‘, ‘class A‘]]

2.822

10236

\[ {}\left (2 y-x \right ) y^{\prime }-y-2 x = 0 \]

[[_homogeneous, ‘class A‘], _exact, _rational, [_Abel, ‘2nd type‘, ‘class A‘]]

4.567

10237

\[ {}\left (2 y-6 x \right ) y^{\prime }-y+3 x +2 = 0 \]

[[_homogeneous, ‘class C‘], _rational, [_Abel, ‘2nd type‘, ‘class A‘]]

1.985

10238

\[ {}\left (4 y+2 x +3\right ) y^{\prime }-2 y-x -1 = 0 \]

[[_homogeneous, ‘class C‘], _rational, [_Abel, ‘2nd type‘, ‘class A‘]]

1.871

10239

\[ {}\left (4 y-2 x -3\right ) y^{\prime }+2 y-x -1 = 0 \]

[[_homogeneous, ‘class C‘], _rational, [_Abel, ‘2nd type‘, ‘class A‘]]

1.879

10240

\[ {}\left (4 y-3 x -5\right ) y^{\prime }-3 y+7 x +2 = 0 \]

[[_homogeneous, ‘class C‘], _exact, _rational, [_Abel, ‘2nd type‘, ‘class A‘]]

3.937

10241

\[ {}\left (4 y+11 x -11\right ) y^{\prime }-25 y-8 x +62 = 0 \]

[[_homogeneous, ‘class C‘], _rational, [_Abel, ‘2nd type‘, ‘class A‘]]

4.007

10242

\[ {}\left (12 y-5 x -8\right ) y^{\prime }-5 y+2 x +3 = 0 \]

[[_homogeneous, ‘class C‘], _exact, _rational, [_Abel, ‘2nd type‘, ‘class A‘]]

3.799

10243

\[ {}a y y^{\prime }+b y^{2}+f \left (x \right ) = 0 \]

[_Bernoulli]

2.245

10244

\[ {}\left (a y+b x +c \right ) y^{\prime }+\alpha y+\beta x +\gamma = 0 \]

[[_homogeneous, ‘class C‘], _rational, [_Abel, ‘2nd type‘, ‘class A‘]]

9.292

10245

\[ {}x y y^{\prime }+y^{2}+x^{2} = 0 \]

[[_homogeneous, ‘class A‘], _rational, _Bernoulli]

5.246

10246

\[ {}x y y^{\prime }-y^{2}+a \,x^{3} \cos \left (x \right ) = 0 \]

[[_homogeneous, ‘class D‘], _Bernoulli]

3.471

10247

\[ {}x y y^{\prime }-y^{2}+x y+x^{3}-2 x^{2} = 0 \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

1.219

10248

\[ {}\left (x y+a \right ) y^{\prime }+b y = 0 \]

[[_1st_order, _with_exponential_symmetries], _rational, [_Abel, ‘2nd type‘, ‘class B‘]]

1.006

10249

\[ {}x \left (y+4\right ) y^{\prime }-y^{2}-2 y-2 x = 0 \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

4.273

10250

\[ {}x \left (y+a \right ) y^{\prime }+b y+c x = 0 \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

0.931

10251

\[ {}\left (\left (x +y\right ) x +a \right ) y^{\prime }-y \left (x +y\right )-b = 0 \]

[[_1st_order, _with_linear_symmetries], _rational, [_Abel, ‘2nd type‘, ‘class B‘]]

1.324

10252

\[ {}\left (x y-x^{2}\right ) y^{\prime }+y^{2}-3 x y-2 x^{2} = 0 \]

[[_homogeneous, ‘class A‘], _rational, [_Abel, ‘2nd type‘, ‘class B‘]]

4.937

10253

\[ {}2 x y y^{\prime }-y^{2}+a x = 0 \]

[[_homogeneous, ‘class G‘], _rational, _Bernoulli]

1.327

10254

\[ {}2 x y y^{\prime }-y^{2}+a \,x^{2} = 0 \]

[[_homogeneous, ‘class A‘], _rational, _Bernoulli]

3.928

10255

\[ {}2 x y y^{\prime }+2 y^{2}+1 = 0 \]

[_separable]

2.487

10256

\[ {}x \left (2 y+x -1\right ) y^{\prime }-y \left (y+2 x +1\right ) = 0 \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

1.492

10257

\[ {}x \left (2 y-x -1\right ) y^{\prime }+y \left (2 x -y-1\right ) = 0 \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

1.477

10258

\[ {}\left (2 x y+4 x^{3}\right ) y^{\prime }+y^{2}+112 x^{2} y = 0 \]

[[_homogeneous, ‘class G‘], _rational, [_Abel, ‘2nd type‘, ‘class B‘]]

2.465

10259

\[ {}x \left (3 y+2 x \right ) y^{\prime }+3 \left (x +y\right )^{2} = 0 \]

[[_homogeneous, ‘class A‘], _rational, [_Abel, ‘2nd type‘, ‘class B‘]]

8.134

10260

\[ {}\left (2+3 x \right ) \left (y-2 x -1\right ) y^{\prime }-y^{2}+x y-7 x^{2}-9 x -3 = 0 \]

[[_homogeneous, ‘class C‘], _rational, [_Abel, ‘2nd type‘, ‘class B‘]]

3.687

10261

\[ {}\left (6 x y+x^{2}+3\right ) y^{\prime }+3 y^{2}+2 x y+2 x = 0 \]

[_exact, _rational, [_Abel, ‘2nd type‘, ‘class B‘]]

1.437

10262

\[ {}\left (y a x +b \,x^{n}\right ) y^{\prime }+\alpha y^{3}+\beta y^{2} = 0 \]

[_rational, [_1st_order, ‘_with_symmetry_[F(x)*G(y),0]‘], [_Abel, ‘2nd type‘, ‘class C‘]]

5.023

10263

\[ {}\left (B x y+A \,x^{2}+a x +b y+c \right ) y^{\prime }-B g \left (x \right )^{2}+A x y+\alpha x +\beta y+\gamma = 0 \]

[[_Abel, ‘2nd type‘, ‘class B‘]]

7.902

10264

\[ {}\left (x^{2} y-1\right ) y^{\prime }+x y^{2}-1 = 0 \]

[_exact, _rational, [_Abel, ‘2nd type‘, ‘class B‘]]

1.316

10265

\[ {}\left (x^{2} y-1\right ) y^{\prime }-x y^{2}+1 = 0 \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

1.615

10266

\[ {}\left (x^{2} y-1\right ) y^{\prime }+8 x y^{2}-8 = 0 \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

1.109

10267

\[ {}x \left (x y-2\right ) y^{\prime }+x^{2} y^{3}+x y^{2}-2 y = 0 \]

[[_homogeneous, ‘class G‘], _rational, [_Abel, ‘2nd type‘, ‘class C‘]]

2.608

10268

\[ {}x \left (x y-3\right ) y^{\prime }+x y^{2}-y = 0 \]

[[_homogeneous, ‘class G‘], _rational, [_Abel, ‘2nd type‘, ‘class B‘]]

2.091

10269

\[ {}x^{2} \left (-1+y\right ) y^{\prime }+\left (x -1\right ) y = 0 \]

[_separable]

1.587

10270

\[ {}x \left (x y+x^{4}-1\right ) y^{\prime }-y \left (x y-x^{4}-1\right ) = 0 \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

1.191

10271

\[ {}2 x^{2} y y^{\prime }+y^{2}-2 x^{3}-x^{2} = 0 \]

[[_homogeneous, ‘class D‘], _rational, _Bernoulli]

2.370

10272

\[ {}2 x^{2} y y^{\prime }-y^{2}-x^{2} {\mathrm e}^{x -\frac {1}{x}} = 0 \]

[_Bernoulli]

2.218

10273

\[ {}\left (2 x^{2} y+x \right ) y^{\prime }-x^{2} y^{3}+2 x y^{2}+y = 0 \]

[[_homogeneous, ‘class G‘], _rational, [_Abel, ‘2nd type‘, ‘class C‘]]

2.644

10274

\[ {}\left (2 x^{2} y-x \right ) y^{\prime }-2 x y^{2}-y = 0 \]

[[_homogeneous, ‘class G‘], _rational, [_Abel, ‘2nd type‘, ‘class B‘]]

1.958

10275

\[ {}\left (2 x^{2} y-x^{3}\right ) y^{\prime }+y^{3}-4 x y^{2}+2 x^{3} = 0 \]

[[_homogeneous, ‘class A‘], _rational, [_Abel, ‘2nd type‘, ‘class C‘], _dAlembert]

23.888

10276

\[ {}2 x^{3}+y y^{\prime }+3 x^{2} y^{2}+7 = 0 \]

[_rational, _Bernoulli]

2.746

10277

\[ {}2 x \left (x^{3} y+1\right ) y^{\prime }+\left (3 x^{3} y-1\right ) y = 0 \]

[[_homogeneous, ‘class G‘], _rational, [_Abel, ‘2nd type‘, ‘class B‘]]

2.270

10278

\[ {}\left (x^{n \left (n +1\right )} y-1\right ) y^{\prime }+2 \left (n +1\right )^{2} x^{n -1} \left (x^{n^{2}} y^{2}-1\right ) = 0 \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

5.125

10279

\[ {}\left (y-x \right ) \sqrt {x^{2}+1}\, y^{\prime }-a \sqrt {\left (1+y^{2}\right )^{3}} = 0 \]

[‘x=_G(y,y’)‘]

563.217

10280

\[ {}y y^{\prime } \sin \left (x \right )^{2}+y^{2} \cos \left (x \right ) \sin \left (x \right )-1 = 0 \]

[_exact, _Bernoulli]

6.309

10281

\[ {}f \left (x \right ) y y^{\prime }+g \left (x \right ) y^{2}+h \left (x \right ) = 0 \]

[_Bernoulli]

2.448

10282

\[ {}\left (g_{1} \left (x \right ) y+g_{0} \left (x \right )\right ) y^{\prime }-f_{1} \left (x \right ) y-f_{2} \left (x \right ) y^{2}-f_{3} \left (x \right ) y^{3}-f_{0} \left (x \right ) = 0 \]

[[_Abel, ‘2nd type‘, ‘class C‘]]

107.246

10283

\[ {}\left (y^{2}-x \right ) y^{\prime }-y+x^{2} = 0 \]

[_exact, _rational]

1.276

10284

\[ {}\left (x^{2}+y^{2}\right ) y^{\prime }+2 x \left (y+2 x \right ) = 0 \]

[[_homogeneous, ‘class A‘], _exact, _rational, _dAlembert]

5.052

10285

\[ {}\left (x^{2}+y^{2}\right ) y^{\prime }-y^{2} = 0 \]

[[_homogeneous, ‘class A‘], _rational, _dAlembert]

5.747

10286

\[ {}\left (y^{2}+x^{2}+a \right ) y^{\prime }+2 x y = 0 \]

[_exact, _rational, [_1st_order, ‘_with_symmetry_[F(x)*G(y),0]‘]]

1.122

10287

\[ {}\left (y^{2}+x^{2}+a \right ) y^{\prime }+2 x y+x^{2}+b = 0 \]

[_exact, _rational]

1.405

10288

\[ {}\left (y^{2}+x^{2}+x \right ) y^{\prime }-y = 0 \]

[_rational]

1.270

10289

\[ {}\left (y^{2}-x^{2}\right ) y^{\prime }+2 x y = 0 \]

[[_homogeneous, ‘class A‘], _rational, _dAlembert]

5.288

10290

\[ {}\left (y^{2}+x^{4}\right ) y^{\prime }-4 x^{3} y = 0 \]

[[_homogeneous, ‘class G‘], _rational]

2.676

10291

\[ {}\left (y^{2}+4 \sin \left (x \right )\right ) y^{\prime }-\cos \left (x \right ) = 0 \]

[[_1st_order, ‘_with_symmetry_[F(x)*G(y),0]‘]]

2.174

10292

\[ {}\left (y^{2}+2 y+x \right ) y^{\prime }+\left (x +y\right )^{2} y^{2}+y \left (1+y\right ) = 0 \]

[_rational]

3.526

10293

\[ {}\left (x +y\right )^{2} y^{\prime }-a^{2} = 0 \]

[[_homogeneous, ‘class C‘], _dAlembert]

4.967

10294

\[ {}\left (y^{2}+2 x y-x^{2}\right ) y^{\prime }-y^{2}+2 x y+x^{2} = 0 \]

[[_homogeneous, ‘class A‘], _rational, _dAlembert]

6.351

10295

\[ {}\left (y+3 x -1\right )^{2} y^{\prime }-\left (2 y-1\right ) \left (4 y+6 x -3\right ) = 0 \]

[[_homogeneous, ‘class C‘], _rational]

3.543

10296

\[ {}3 \left (y^{2}-x^{2}\right ) y^{\prime }+2 y^{3}-6 x \left (x +1\right ) y-3 \,{\mathrm e}^{x} = 0 \]

[‘y=_G(x,y’)‘]

2.178

10297

\[ {}\left (4 y^{2}+x^{2}\right ) y^{\prime }-x y = 0 \]

[[_homogeneous, ‘class A‘], _rational, _dAlembert]

3.723

10298

\[ {}\left (4 y^{2}+2 x y+3 x^{2}\right ) y^{\prime }+y^{2}+6 x y+2 x^{2} = 0 \]

[[_homogeneous, ‘class A‘], _exact, _rational, _dAlembert]

7.264

10299

\[ {}\left (2 y-3 x +1\right )^{2} y^{\prime }-\left (3 y-2 x -4\right )^{2} = 0 \]

[[_homogeneous, ‘class C‘], _rational]

36.895

10300

\[ {}\left (2 y-4 x +1\right )^{2} y^{\prime }-\left (y-2 x \right )^{2} = 0 \]

[[_homogeneous, ‘class C‘], _rational, _dAlembert]

2.243